Causality of Inflation and Unemployment In Lampung Province - Kusuma, A. Fadillah Putra (MSJ : Majority Science Journal, 2024)
Inflation and unemployment are major economic challenges in Indonesia that are often influenced by sub-optimal economic growth. This study aims to examine the causality relationship between inflation and unemployment with a focus on Lampung Province. The methodology used is descriptive and quantitative, with secondary data analysis from the Central Bureau of Statistics (BPS) for the period 1990-2023. The Granger causality test results show a one-way relationship, where inflation affects unemployment, with a Prob probability value of 0.02787 which is less than 0.05. This finding suggests the existence of a long-run causality relationship between inflation and unemployment, which is reinforced by the cointegration test results, where the probability values for both variables are also below 0.05. This study provides an in-depth insight into the interaction between inflation and unemployment and its implications for regional economic policy, which can help in formulating strategies to overcome economic problems in Lampung Province.